Differentiating among stages of cognitive impairment in aging: Version 3 of the Uniform Data Set (UDS) neuropsychological test battery and MoCA index scores. Issue 1 (24th November 2020) - Dodge, Hiroko H.; Goldstein, Felicia C.; Wakim, Nicole I; Gefen, Tamar; Teylan, Merilee; Chan, Kwun C.G.; Kukull, Walter A.; Barnes, Lisa L.; Giordani, Bruno; Hughes, Timothy M.; Kramer, Joel H.; Loewenstein, David A.; et al.
Abstract: Introduction: Federally funded Alzheimer's Disease Centers in the United States have been using a standardized neuropsychological test battery as part of the National Alzheimer's Coordinating Center Uniform Data Set (UDS) since 2005. Version 3 (V3) of the UDS replaced the previous version (V2) in 2015. We compared V2 and V3 neuropsychological tests with respect to their ability to distinguish among the Clinical Dementia Rating (CDR) global scores of 0, 0.5, and 1. Methods: First, we matched participants receiving V2 tests (V2 cohort) and V3 tests (V3 cohort) in their cognitive functions using tests common to both versions. Then, we compared receiver‐operating characteristic (ROC) area under the curve in differentiating CDRs for the remaining tests. Results: Some V3 tests performed better than V2 tests in differentiating between CDR 0.5 and 0, but the improvement was limited to Caucasian participants. Discussion: Further efforts to improve the ability for early identification of cognitive decline among diverse racial groups are required.